Nurse Family Partnership: Comparing Costs per Family in Randomized Trials Versus Scale-Up - Miller, Ted; Hendrie, Delia (Springer, 2015)
The literature that addresses cost differences between randomized trials and full-scale repli- cations is quite sparse. This paper examines how costs differed among three randomized trials and six statewide scale-ups of nurse family partnership (NFP) intensive home visitation to low income first- time mothers. A literature review provided data on pertinent trials. At our request, six well-established programs reported their total expenditures. We adjusted the costs to national prices based on mean hourly wages for registered nurses and then inflated them to 2010 dollars. A centralized data system provided utilization. Replications had fewer home visits per family than trials (25 vs. 31, p = .05), lower costs per client ($8860 vs. $12,398, p = .01), and lower costs per visit ($354 vs. $400, p = .30). Sample size limited the significance of these differences. In this type of labor intensive program, costs probably were lower in scale-up than in randomized trials. Key cost drivers were attrition and the stable caseload size possible in an ongoing program. Our estimates reveal awide variation in cost per visit across six state programs, which suggests that those planning replications should not expect a simple rule to guide cost estimations for scale-ups. Nevertheless, NFP replications probably achieved some economies of scale.